EMOTIONS OF CHILD ABUSE VICTIMS: A STUDY ON THE NOVEL KOIN ROKKA BEIBIZU - Tienn Immerry; Femmy Dahlan; Yulia Yulia; Eduardus Agusli (LLDIKTI Wilayah X, 2024)
There is a unique form of child abuse in Japan. Mothers abandoned newborn babies (alive or stillborn) in a coin locker, famously known as koin rokkaa beibizu (coin locker babies). This research aims to reveal the levels of Kiku and Hashi’s (the coin locker babies) angry emotions from the least intense to the most intense. This research applied a qualitative method as a process of research and understanding based on a methodology that investigates social phenomena and human problems. Data analysis utilizes Parrot’s theory of emotions. In conclusion, Kiku and Hashi’s emotions are all explicit. Kiku and Hashi underwent three levels of anger, from tertiary to primary. The children’s anger implicitly derives from their mothers’ negligence. As the victims of child abuse, Kiku and Hashi became emotionally disturbed children. Kiku and Hashi experienced a phase of anger (primary emotion) and became depersonalized. Kiku and Hashi’s anger continued to spread massive damage.